ANALISIS GAYA HIDUP SEBAGAI FAKTOR RESIKO HIPERTENSI DI DESA MLIWIS CEPOGO BOYOLALI - Lilik Sriwiyati; Dwi Indriani (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : hypertension is blood pressure with systolic pressure above 140 mmHgand diastolic pressure above 90 mmHg. Hypertension risk factors vary widely. Healthylifestyle, such as attention to body, mind, and a healthy soul can reduce the risk ofhypertension. The purpose of this study was to analyze lifestyle as hypertension riskfactor in Mliwis, Cepogo, Boyolali.Methods of the research is a corelational study. Subjects of this research were Mliwisvillagers. The samples were 46 responden selected by using purposive sampling method.Collecting data use questionnaire paper. Data analysis use logistic regresion test withp=0,05Results of this research is high salt eating habits is the most influential risk factor tohypertension, that is with value p = 0,013, OR 35.181 ; CI 95 % 2,096 until 590,563. Thenfollowed by variable smoking habit (p = 0.017, OR 24.920 ; CI 95 % 1.758 hingga 353.31)and sports habits (p = 0.041, OR 0.062 ; CI 95 % 0.004 hingga 0.893). Variable habit ofdrinking alcohol, eating high fat and obesity have no effect on hypertension. Statisticaltest results of these variables are: drinking alcohol p = 0,079, OR 19,003 ; CI 95 % 0,711until 507,940), eating high fat (p = 0,675, OR 1,597 ; CI 95 % 0,179 until 14,283), obesity(p = 0,404, OR 2,766 ; CI 95 % 0,253 until 30,194). The value of Negelkerke R Square is66.9 %.Conclusion : lifestyle that increases the risk of hypertension is a high salt eating habits,smoking habits and exercise habits, while the habit of drinking alcohol, eating high fatand obesity have no effect increase the risk of hypertension on villagers of Mliwis CepogoBoyolali.Keywords: lifestyle, high salt eating habits, smoking habits, exercise habits, habit ofdrinking alcohol, eating high fat and obesity, hypertension